2002
DOI: 10.1673/031.002.0501
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses of adult female tobacco hornworms, Manduca sexta, to hostplant volatiles change with age and mating status

Abstract: We present evidence for two behaviors influenced by intact, vegetative plant odor — upwind flight and abdomen curling — in female Manduca sexta and demonstrate the influence of the age and mating status of the moths on these behaviors. We compared the behavioral responses of laboratory-reared M. sexta . of discrete ages and physiological states (2,3, and 4 day old for virgin; 2 and 3 day old for mated) as individual moths flew upwind in a flight tunnel to a source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Linalool is a common component of the scent of moth-pollinated flowers (Miyake et al 1998;Raguso & Pichersky 1999), and (þ)-linalool is the major floral component in the moth-pollinated Clarkia breweri (Raguso & Pichersky 1999). While foliage volatiles from host plants are sufficient to elicit oviposition in laboratory experiments (Mechaber et al 2002), it is possible that in nature floral (þ)-linalool acts in concert with foliage volatiles to attract M. sexta from a distance and/or at close range to elicit oviposition behaviour. If so, then the effects of (þ)-linalool parallel the reported scale-dependent effects of CO 2 on visits of hungry M. sexta moths to D. wrightii flowers (Goyret et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Linalool is a common component of the scent of moth-pollinated flowers (Miyake et al 1998;Raguso & Pichersky 1999), and (þ)-linalool is the major floral component in the moth-pollinated Clarkia breweri (Raguso & Pichersky 1999). While foliage volatiles from host plants are sufficient to elicit oviposition in laboratory experiments (Mechaber et al 2002), it is possible that in nature floral (þ)-linalool acts in concert with foliage volatiles to attract M. sexta from a distance and/or at close range to elicit oviposition behaviour. If so, then the effects of (þ)-linalool parallel the reported scale-dependent effects of CO 2 on visits of hungry M. sexta moths to D. wrightii flowers (Goyret et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pheromone-specific MGC-ORNs maintain certain glycosylation patterns into adulthood . At the behavioral level, adult female M. sexta exhibit changing responses to host plant volatiles, depending on age and mating status (Mechaber et al 2002). The underlying principle might be comparable to that in males, since the female glomeruli specialized to host plant odors correspond to the MGC in males (Rospars and Hildebrand 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, our results support the hypothesis that CO 2 acts as an orientation stimulus (Table 1, H A1 ). The CO 2 plume evoked the typical zigzag casting flight pattern indicative of odor-guided behavior in M. sexta (30,47,48) and was slightly more likely to elicit upwind casting flight than was floral odor. These results suggest that floral CO 2 is perceived by M. sexta as an odor, a hypothesis that is consistent with the fact that CO 2 -receptor cells in the LPO project their axons through the suboesophageal ganglion into both antennal lobes (34), the primary centers for the processing of olfactory inputs from the antennae.…”
Section: Scale Dependence Of Responses To Co2 In No-choice Assaysmentioning
confidence: 95%
“…3). Mechaber et al (48) demonstrated that virgin female M. sexta show host-plant tracking behavior in response to tomato leaf volatiles, and abdominal curling typical of oviposition when in contact with the plant, 3 days after eclosion. Thus, our unmated females-all of them 3 or more days posteclosion-were expected to show some response to host-plant volatiles.…”
Section: Context Dependence Of Female Responses In Binary-choice Assaysmentioning
confidence: 99%